Defining Culinary Authority : The Transformation of Cooking in France, 1650-1830 - Davis, Jennifer J. (Book collections on Project MUSE., 2013)
In the eighteenth and nineteenth centuries, French cooks began to claim central roles in defining and enforcing taste, as well as in educating their diners to changing standards. Tracing the transformation of culinary trades in France during the Revolutionary era, the author argues that the work of cultivating sensibility in food was not simply an elite matter; it was essential to the livelihood of thousands of men and women. Combining rigorous archival research with social history and cultural studies, the author analyzes the development of cooking aesthetics and practices by examining the propagation of taste, the training of cooks, and the policing of the culinary marketplace in the name of safety and good taste.